Consumer response on X2 coloured contact lens (A case study at PT alergan inti Indonesia in Jakarta as the of X2 coloured contact lens distributor) - Budi, Haryono (Đại học Kinh tế, 2016)
Branding has been around for centuries as a means to distinguish the goods of one producer from those of another. A brand is a name, term, sign, symbol, or design, or a combination of them, intended to identify the goods and services of one seller or group of sellers and to differentiate them from those of competition, then, whenever a marketer creates a new name, logoor symbol for a new product, he or she has created a brand. It should being recognized that many practicing managers, however, refer to a brand as more than that, defining a brand in terms of having actually created a certain amount of awareness, reputation, prominence, and so on in the market place. The key to creating a brand is to be able to choose a name, logo, symbol, package design, or other attribute that identifies a product and distinguishes it from others